Thermal analysis by TGA and DTA method of wood-polymer of furfurylated beech and fir wood - Aisona Talaei (تحقیقات علوم چوب و کاغذ ایران, 2019)
The present study was carried out with the aim of thermal analysis of furfurylated wood produced from beech (Fagus orientalis) and fir (Abies alba). In this regard, the specimens were saturated with two different levels of furfurylation in the form of low levels (14% fir and 20% beech) and high levels (38% fir and 65% beech), and compared with control samples. The results showed that changes in the TGA and DTA thermograms occur with an increase in the furfurylation level. In the first section of TGA graphs, thermal stability of the wood increased with furfurylation and its level change due to decreased water absorption and evaporation of gases during the process of furfurylation. But in the second and third regions, because of the replacement of furfuryl alcohol with lower thermal stability and flammability in the structure of wood and changes in the chemical structure of the wood, the thermal stability of wood polymers in both species decreased. The results of the analysis of DTA thermograms, in addition to confirming the findings from the TGA analysis, made clear the results of the impact of wood species on the thermal stability of wood polymers. Due to the difference in cellulose and hemicellulose and lignin in the structure of softwoods and hardwoods, the hemi-cellulose type in two species and the thermal stability difference of different implementation, wood polymers from two beech and fir are different in the variation of the surface under the curve of the DTA thermograms, the initial temperatures and peak temperatures.